Though not dead - Stabenow, Dana (Stabenow, Dana. Kate Shugak series., 2011)
Inheriting a homestead from her late uncle, a stunned Kate Shugak receives a cryptic letter from him imploring her to discover his father's fate, a mystery involving a priceless tribal artifact for which Kate is targeted by murderous attacks.